Technological surveillance: Arkangel in frames (2019)
This paper analyzes some frames of the TV series Black Mirror, episode Arkangel. According to some theoretical lines of contemporary scholars such as Deleuze, Bauman and Han, there are different situations that relate control and surveillance to childhood, which is tracked by technological devices. The social consequences occur in the near future determined by technology as a center of the virtual monitoring mechanisms. The work methodology is based on a bibliographic review and a theoretical reflection about the analyzed episode. The work scheme has been articulated in five frames, as follows: from the spoiler to the philosophy, the relation between childhood and technological influence, the interactions between technology and surveillance, the diverse properties and consequences and, lastly, the techno-dependence. At the end, there are some considerations that allow us to raise new questions.